A dictionary of the Ugaritic language in the alphabetic tradition - Olmo Lete, Gregorio del. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2015)
As with any dictionary of a newly discovered dead language, the aim of this Dictionary of the Ugaritic alphabetic texts is to indicate the stage reached in its lexical description and to serve as a reference work for further study. In this connection, the main interpretative opinions have been included, since to a large extent Ugaritic lexicography remains uncertain. Also the most relevant comparative Semitic material has been provided in order to corroborate the lexical choices adopted by the authors and help readers to verify their own. The new material discovered since 1992 and recently published has also been included, along with all the personal and topographical names as in the two previous editions.